2007
DOI: 10.1002/pssb.200642327
|View full text |Cite
|
Sign up to set email alerts
|

The way composition affects martensitic transformation temperatures of Ni–Mn–Ga Heusler alloys

Abstract: A systematic substitution of Ge, Si, C and Co for Ga in the non-stoichiometric Ni -Mn -Ga alloys was performed. The relationship between the compositions of different elements including Ni, Mn, Ga, Ge, Si, C, Co, In and martensitic transformation temperature (M s ) was studied in detail for the present alloys together with data collected from a variety of sources. It is found that M s is a sensitive parameter to the composition. The size factor and electron concentration are usually thought to be the way the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“…In such a case, the system tends to minimize the free energy by creating the distortions. The new Brillouin zone pattern corresponds to the new crystal structure, which is martensite [29,30]. The increase in the density of the valance electron number leads to a higher M s , and depending on the excess in the conduction electrons at the Fermi level, the 5M, 7M or L10 martensite structures form.…”
Section: Discussionmentioning
confidence: 98%
“…In such a case, the system tends to minimize the free energy by creating the distortions. The new Brillouin zone pattern corresponds to the new crystal structure, which is martensite [29,30]. The increase in the density of the valance electron number leads to a higher M s , and depending on the excess in the conduction electrons at the Fermi level, the 5M, 7M or L10 martensite structures form.…”
Section: Discussionmentioning
confidence: 98%
“…Khan et al [62] specifically studied the effect of isoelectronic substitution of Ga by In in Ni 2 MnGa and concluded that the effect of Z on M s mainly arise from the change of unit cell volume which modifies the relative position of the Brillouin zone boundary and Fermi surfaces. The role of volume effects on the martensitic transition has been further studied via doping of Ni-Mn-Ga with several other elements and use of electron density to parametrize structural transition temperatures has been suggested [63,64]. The effect of magnetism on the martensitic transition, however, has been studied in less detail.…”
Section: Discussionmentioning
confidence: 99%
“…19 Here, V cell is the volume of the unit cell and N is the number of atoms contained in the unit cell. On the other hand, the shear modulus C = 1 2 (C 11 − C 12 ) may also serve as the predictor of the composition-dependent T M .…”
Section: Introductionmentioning
confidence: 99%